Genome Sequences of Three Phytopathogenic Species of the Magnaporthaceae Family of Fungi. Issue 12 (1st December 2015) - Okagaki, Laura H; Nunes, Cristiano C; Sailsbery, Joshua; Clay, Brent; Brown, Doug; John, Titus; Oh, Yeonyee; Young, Nelson; Fitzgerald, Michael; Haas, Brian J; Zeng, Qiandong; Young, Sarah; et al.
Abstract: Magnaporthaceae is a family of ascomycetes that includes three fungi of great economic importance: Magnaporthe oryzae, Gaeumannomyces graminis var. tritici, and Magnaporthe poae . These three fungi cause widespread disease and loss in cereal and grass crops, including rice blast disease ( M. oryzae ), take-all disease in wheat and other grasses ( G. graminis ), and summer patch disease in turf grasses ( M. poae ). Here, we present the finished genome sequence for M. oryzae and draft sequences for M. poae and G. graminis var. tritici . We used multiple technologies to sequence and annotate the genomes of M. oryzae, M. poae, and G. graminis var. tritici . The M. oryzae genome is now finished to seven chromosomes whereas M. poae and G. graminis var. tritici are sequenced to 40.0× and 25.0× coverage respectively. Gene models were developed by the use of multiple computational techniques and further supported by RNAseq data. In addition, we performed preliminary analysis of genome architecture and repetitive element DNA.